2014
DOI: 10.3109/1040841x.2014.913004
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicansand cancer: Can this yeast induce cancer development or progression?

Abstract: There is currently increasing concern about the relation between microbial infections and cancer. More and more studies support the view that there is an association, above all, when the causal agents are bacteria or viruses. This review adds to this, summarizing evidence that the opportunistic fungus Candida albicans increases the risk of carcinogenesis and metastasis. Until recent years, Candida spp. had fundamentally been linked to cancerous processes as it is an opportunist pathogen that takes advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 155 publications
0
113
0
7
Order By: Relevance
“…Although Th17 cells are shown to be pathological mediators in several oral diseases, whether chronic activation of Th17 cells is pathogenic in OPC remain to be investigated. With recent findings implying the role of C. albicans in inflammation and cancer, Th17 immunopathology in the oral cavity is an active field of investigation 31 . Thus the model that is described here can be used to more carefully study specific roles of Th17 cells and how they interact with innate immune cells, giving detailed insights in to oral immunological diseases and oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although Th17 cells are shown to be pathological mediators in several oral diseases, whether chronic activation of Th17 cells is pathogenic in OPC remain to be investigated. With recent findings implying the role of C. albicans in inflammation and cancer, Th17 immunopathology in the oral cavity is an active field of investigation 31 . Thus the model that is described here can be used to more carefully study specific roles of Th17 cells and how they interact with innate immune cells, giving detailed insights in to oral immunological diseases and oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This ratio is important for carcinogenesis. Ramirez-Garcia et al [28] indicated that the opportunistic fungus C. albicans increases the risk of carcinogenesis and metastasis. C. albicans is capable of promoting cancer by several mechanisms: the production of carcinogenic byproducts, triggering of inflammation, induction of Th17 responses and molecular mimicry.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, epidemiological studies suggest that fungal infection is associated with certain types of human cancers. [115][116][117] Candida albicans is frequently found in the lesion sets of diseases or cancers in humans, [59,118] but many other fungi, including Cladosporium cladosporioides and Candida tropicalis, were also reported in human solid cancers. As discussed above, IKK/NF-kB-regulated immunity plays a decisive role in defending against infections.…”
Section: Fungal Infection and Carcinogenesismentioning
confidence: 99%